Organocatalytic Approach to the Enantioselective Total Synthesis of (+)-Serinolamides A and B and (+)-Lacosamide - Jadhao, Amardeep R.; Waghmode, Suresh B. (Synthesis, 2024)
A short and highly efficient enantioselective synthesis of (+)-serinolamide A, B and (+)-lacosamide from 3-methoxypropanal using l-proline-catalyzed α-amination, Grubbs metathesis, and acid-amine coupling as key steps is reported.
Keywords: enantioselective; l-proline-catalyzed; asymmetric α-amination; serinolamide A, B and lacosamide